Avaliação in vitro da atividade antileishmania da zerumbona - (:unkn) unknown (Universidade Federal do Amazonas - Instituto Nacional de Pesquisas da Amazônia, 2018)
American Cutaneous Leishmaniasis (ACL) is a non-contagious infectious disease that affects the protozoa of the genus Leishmania. Approximately 98 have already reported a disease, affecting 12 million people worldwide. The patients with ATL in the clinical setting differed, manifesting in cutaneous and mucosal form. The treatment of the disease in Brazil makes use of drugs of first and second choice, being represented by pentavalent antimonials and like other drugs as the treatment over the years. It is a possibility of attention to be considered as a clinical condition for lesions, a possibility for drugs, a geographical location in which a species of infectious Leishmania was captured. Since then, the drugs have high toxicity, are adverse adverse, some species are needed and are required for parenteral administration. In this context, it is necessary to search for new compositions that have antileishmania activity that demonstrate e-mail and security, facilitating the treatment of the disease. Studies with a zerumba, a sesquiterpene found in Zingiber zerumbet (L.) Roscoe ex Sm., Demonstrated a great accumulation of biomedical properties, focused on a great interest of the scientific community in the possibility of the use of talent for the treatment of cutaneous leishmaniasis. This study is the study of the sigma-aluminum assay in the antigenishmania in antileishmaniasis in the shigellostigotes and amastigotes of Leishmania (Leishmania) amazonensis and Leishmania (Viannia) guyanensis and the cytotoxicity against murine peritoneal macrophages. To evaluate the activity of zerumba against promastigote forms of parasites were exposed to the material under study at concentrations of 0.250 - 0.015 mg / mL, for 48 to 72 hours for L. (V.) Guyanensis and 72 to 96 hours for L. ( L.) amazonensis. A cytotoxic activity against murine peritoneal macrophages was evaluated. For the evaluation of the amastigotes, peritoneal macrophages, the murine ones were submitted to infection by the promastigote forms of the species under study and were exposed at concentrations of 0.250 - 0.031 mg / ml for 48 to 72 hours for L. (V.) Guyanensis and 72 to 96 hours for L. (L.) amazonensis is an evaluation of cell morphology and determination of infection rate. Bioassays indicated that zerumbone shows toxicity to the cellular model under study at concentrations of 0.250 mg / mL and 0.125 mg / mL. Although the mechanism of action is not defined, it is suggested that DNA condensation or oxidative stress lead the cell to undergo apoptosis. It promotes antileishmania activity against promastigotes of both species with EC50 capable of reducing more than 50% of parasite growth during the entire incubation period. The bioassays against amastigote forms for the species L. (L.) amazonensis (72 and 96h) and L. (V.) guyanensis (48 and 72h) presented antileishmania activity and the inhibition of up to 50% of the infection rate was evaluated for both species. For the first time, zerumbone activity against promastigotes and amastigotes of the target species of this study has shown promise for both species, which encourages us to continue the in vivo tests for ACL treatment.
In vitro evaluation of antileishmanial activity of zerumbon
Keywords: Leishmaniose - Tratamento; Produtos naturais - Uso terapêutico; CIENCIAS DA SAUDE; Leishmania; Zerumbona; In Vitro; Produtos Naturais